Impact of pandemic COVID-19 in the global south and political response on the economy: a study on selected African countries - Rena, R.; Yadav, U.Sh. (Journal of Economic Research & Business Administration, 2024)
The purpose of this paper is to examine how COVID-19 has affected the Global South and what major response was given by the policymakers to improve the pandemic situation and improve the economy of the Global south specially in selected countries in Africa. It explores the social and economic effects that pre-existing structures, inadequate political responses, and several crises, along with other variables. This pandemic had created significant adverse effects on the Global South economies. The shutdown declared by countries at the world level and its effect on business in commodity, tourism, service sector, education, and money flows have all had an impact on the gross domestic product (GDP). Those countries experience adverse effects that are vulnerable in all sectors in the middle lockdown term due to adverse implementation of their policy and less resourced supply to their population. Additionally, COVID -19 is having negative social effects like the emergence of new susceptible and increased inequality among the people. This paper discusses some of the policies implemented by the Global South at the time of the pandemic crisis, and their effects on the population which is also characterized by their inability to access domestic resources and their restricted ability to access foreign financial resources. Key words: Global south, pandemic, COVID -19, political economy, gender disparity, unorganized sector, financial resources, African countries.